Metabolic syndrome biomarkers and prostate cancer risk in the UK Biobank. Issue 4 (11th September 2020) - Monroy‐Iglesias, Maria J.; Russell, Beth; Crawley, Danielle; Allen, Naomi E.; Travis, Ruth C.; Perez‐Cornago, Aurora; Van Hemelrijck, Mieke; Beckmann, Kerri
Abstract: We investigated the association between metabolic syndrome (MetS) and its components and risk of prostate cancer (PCa) in a cohort of men enrolled in the UK Biobank. Our study cohort included 220 622 PCa‐free men with baseline measurements of triglycerides (TGs), HDL‐cholesterol (HDL), glycated hemoglobin (HbA1c), blood pressure (BP), and waist circumference (WC). Multivariable Cox proportional hazards regression was used to analyze associations with PCa for: individual metabolic components (TG, HDL, HbA1c, BP, WC), combinations of two and three components, and MetS overall (three or more components). We conducted mediation analyses to examine potential hormonal and inflammatory pathways (total testosterone [TT], C‐reactive protein [CRP], insulin‐like growth factor 1 [IGF‐1]) through which MetS components may influence PCa risk. A total of 5409 men in the study developed PCa during a median follow‐up of 6.9 years. We found no significant association between MetS and PCa risk (hazard ratio [HR] = 0.99, 95% confidence interval [CI] = 0.92‐1.06). No associations were found with PCa risk and individual measurements of TG, HDL, BP, or WC. However, an inverse association was observed with elevated HbA1c (≥42 mmol/mol) (HR = 0.89, 95% CI = 0.79‐0.98). Consistent inverse associations were observed between HbA1c and risk of PCa. Mediation analysis revealed TT, CRP, and IGF‐1 as potential mediating factors for this association contributing 10.2%, 7.1%, and 7.9% to the total effect, respectively. Overall MetS had no association with PCa risk. However, a consistent inverse association with PCa risk was found for HbA1c. This association may be explained in part through hormonal and inflammatory pathways. Abstract : What's new? Risk of prostate cancer is variously linked to obesity, type 2 diabetes mellitus, and other components of metabolic syndrome (MetS). Evidence for a clear association between prostate cancer and MetS and its components, however, remains elusive. In this large, prospective study, the authors found that MetS is not significantly associated with risk of prostate cancer. Glycated hemoglobin (HbA1c), however, was found to be inversely associated with risk. Analyses examining potential hormonal and inflammatory pathways identified total testosterone, C‐reactive protein, and insulin‐like growth factor 1 as potential mediating factors for the association between HbA1c and prostate cancer.